2023
DOI: 10.1038/s41598-023-39765-4
|View full text |Cite
|
Sign up to set email alerts
|

Eschar dissolution and the immunoregulator effect of keratinase on burn wounds

Yan Xu,
Kai Hu,
Chenyang Liu
et al.

Abstract: At present, enzyme debridement preparation has shown a good curative effect on eschar removal of burn wounds. Keratinase has shown great potential in enzymatic debridement because of its good fibrin-degrading ability. In this study, the debridement of keratinase was examined by using a third degree burn wound model in rats. We observed the wound, and keratinase shortened the time of eschar dissolution after debridement. Histopathology and immunofluorescence staining showed that the eschar in the keratinase gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In another study, Xu et al 78 evaluated the effect of Br in eschar dissolution and the immunoregulator effect of keratinase on burn wounds and demonstrated that by using Br the scratch was completely closed during 12 h.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Xu et al 78 evaluated the effect of Br in eschar dissolution and the immunoregulator effect of keratinase on burn wounds and demonstrated that by using Br the scratch was completely closed during 12 h.…”
Section: Resultsmentioning
confidence: 99%